Nitration of Hsp90 on Tyrosine 33 Regulates Mitochondrial Metabolism - Franco, Maria C. (J Biol Chem, 2015)
Peroxynitrite production and tyrosine nitration are present in several pathological conditions, including neurodegeneration, stroke, aging, and cancer. Nitration of the pro-survival chaperone heat shock protein 90 (Hsp90) in position 33 and 56 induces motor neuron death through a toxic gain-of-function. Here we show that nitrated Hsp90 regulates mitochondrial metabolism independently of the induction of cell death. In PC12 cells, a small fraction of nitrated Hsp90 was located on the mitochondrial outer membrane and down-regulated mitochondrial membrane potential, oxygen consumption, and ATP production. Neither endogenous Hsp90 present in the homogenate nor unmodified and fully active recombinant Hsp90 was able to compete with the nitrated protein for the binding to mitochondria. Moreover, endogenous or recombinant Hsp90 did not prevent the decrease in mitochondrial activity but supported nitrated Hsp90 mitochondrial gain-of-function. Nitrotyrosine in position 33, but not in any of the other four tyrosine residues prone to nitration in Hsp90, was sufficient to down-regulate mitochondrial activity. Thus, in addition to induction of cell death, nitrated Hsp90 can also regulate mitochondrial metabolism, suggesting that depending on the cell type, distinct Hsp90 nitration states regulate different aspects of cellular metabolism. This regulation of mitochondrial homeostasis by nitrated Hsp90 could be of particular relevance in cancer cells.